The importance of CAD and DECT in CT colonography - Wójcik, Anna Monika; Kurzepa, Joanna; Samek, Ilona; Jańczyk, Magdalena; Krawiec, Paulina; Białek, Justyna; Kozioł, Magdalena (Journal of Education, Health and Sport, 2021)
Introduction According to the American College of Radiology and the American Cancer Society, CTC has been recognized as a valuable screening method for detecting CRC in people at medium risk as an alternative to endoscopic colonoscopy. The condition for the proper interpretation of this procedure is the patient’s preparation for the examination. The evaluation of the test includes: topogram, transverse images (as reference images), multifaceted reconstructions and three-dimensional images (3D navigator). Materials and methods The literature on the use of CTC in the diagnosis of CRC was analyzed. A review of the scientific literature indexed in the PUBMED database from the last 10 years was carried out. Results The introduction of dual energy computed tomography (DECT) clearly improved the diagnostic accuracy of CTC. The main advantage of DECT is the possibility of obtaining iodine maps and VNC (virtual non-contrast) – a ’’virtual’’ native image (without the use of contrast). DECT allows you to monitor the results and extent of iodine capture on VNC and iodine map images, respectively, without using pre-recorded tomographic images. Pilot tests showed that DECT is an effective tool in CT colonography diagnostics and electronic colon loop cleaning after barium labeling. The use of the Computer Aided Diagnosis (CAD) algorithm in high energy tomography helps in the diagnosis and detection of intestinal tumors. Conclusions The development of modern technologies used in CT colonography proves that it is a safe and acceptable technique for patients. Lack of invasiveness, low radiation dose and high diagnostic efficiency of CTC may encourage more people to undergo colorectal cancer screening in the future.